2013
DOI: 10.1208/s12249-013-9933-5
|View full text |Cite
|
Sign up to set email alerts
|

An Automated System for Monitoring and Regulating the pH of Bicarbonate Buffers

Abstract: Abstract. The bicarbonate buffer is considered as the most biorelevant buffer system for the simulation of intestinal conditions. However, its use in dissolution testing of solid oral dosage forms is very limited. The reason for this is the thermodynamic instability of the solution containing hydrogen carbonate ions and carbonic acid. The spontaneous loss of carbon dioxide (CO 2 ) from the solution results in an uncontrolled increase of the pH. In order to maintain the pH on the desired level, either a CO 2 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…This medium was replaced by Hanks hydrogen carbonate buffer (pH 6.8) with 0.1 % Tween 80 after 2 h to simulate the pH and the surface tension of fasted state intestinal conditions [33]. The pH value of the bicarbonate buffer was continuously adjusted with an accuracy of ± 0.02 pH units by using the pHysio‐stat system [26]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This medium was replaced by Hanks hydrogen carbonate buffer (pH 6.8) with 0.1 % Tween 80 after 2 h to simulate the pH and the surface tension of fasted state intestinal conditions [33]. The pH value of the bicarbonate buffer was continuously adjusted with an accuracy of ± 0.02 pH units by using the pHysio‐stat system [26]…”
Section: Methodsmentioning
confidence: 99%
“…[33] The pH value of the bicarbonate buffer was continuously adjusted with an accuracy of ± 0.02 pH units by using the pHysio-stat system. [26]…”
Section: Dissolution Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…One method of increasing buffer capacity is to increase buffer concentration; however, this approach may be inconsistent with the physicochemical properties of the simulated biological fluid. Garbacz et al (56) reported on the use of an automated pH-stat system for monitoring and regulating the pH of bicarbonate buffers; however, the use of a pH-stat adds complexity and requires optimizing additional experimental parameters (57).…”
Section: Sufficient Buffer Capacity To Maintain Ph Control Throughoutmentioning
confidence: 99%